2021
DOI: 10.21203/rs.3.rs-419885/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alkalinity Cycling And Carbonate Chemistry Decoupling in Seagrass Mystify Processes of Acidification Mitigation

Abstract: The adverse conditions of acidification on sensitive marine organisms has led to the investigation of bioremediation methods as a way to abate local acidification. This phytoremediation, by macrophytes, is expected to reduce the severity of acidification in nearshore habitats on short timescales. Characterizing the efficacy of phytoremediation can be challenging as residence time, tidal mixing, freshwater input, and a limited capacity to fully constrain the carbonate system can lead to erroneous conclusions. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…The incorporation of other sensors, such as dissolved oxygen concentration into upcoming versions of the SURCOM instrument, or as part of an acidification sensor suite, would represent a significant improvement, as it would allow a better assessment of biological processes and its impacts as drivers for pH oscillations. Recent studies have shown that ecosystem metabolism can cause significant short-term pH changes in addition to being a strong seasonal driver (Feely et al, 2018;Pacella et al, 2018;Lowe et al, 2019;Miller and Kelley, 2021). The information obtained by pH observation networks coupled to other biogeochemical sensors is necessary for understanding the impact of acidification on coastal ecosystems, for the development of predictive models (Mongin et al, 2016;Siedlecki et al, 2016;Turi et al, 2016) and for the design of response strategies to ocean acidification by policy makers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of other sensors, such as dissolved oxygen concentration into upcoming versions of the SURCOM instrument, or as part of an acidification sensor suite, would represent a significant improvement, as it would allow a better assessment of biological processes and its impacts as drivers for pH oscillations. Recent studies have shown that ecosystem metabolism can cause significant short-term pH changes in addition to being a strong seasonal driver (Feely et al, 2018;Pacella et al, 2018;Lowe et al, 2019;Miller and Kelley, 2021). The information obtained by pH observation networks coupled to other biogeochemical sensors is necessary for understanding the impact of acidification on coastal ecosystems, for the development of predictive models (Mongin et al, 2016;Siedlecki et al, 2016;Turi et al, 2016) and for the design of response strategies to ocean acidification by policy makers.…”
Section: Discussionmentioning
confidence: 99%
“…A better analysis of the sources of uncertainty could be approached by deploying an observational mesh of SURCOM sensors over a more long period, that would allow to improve the correction of the impact of the large spatial and temporal variability of these environments, and also to apply different quality control techniques (McLaughlin et al, 2017). In any case, the precision of the SURCOM instrument was comparable to the performance of c o m m e r c i a l pH s e n s o r s f o u n d in s i m i l a r c o a s t a l implementations (Hoppe et al, 2012;Wootton and Pfister, 2012;McLaughlin et al, 2017;Gonski et al, 2018;Miller and Kelley, 2021). Moreover, this uncertainty of ±0.029 is in the range of magnitude to 0.02, an acidification measurement criterion that distinguishes "weather" quality datasets (Newton et al, 2015) proving the potential suitability of this sensor for studies at this level of quality (Gonski et al, 2018) once we gain increased expertise in the equipment and protocols (McLaughlin et al, 2017).…”
Section: Surcom Ph Sensor Performancementioning
confidence: 96%